Can the surface modification and/or morphology affect the ecotoxicity of zinc oxide nanomaterials?. (June 2019) - Melegari, Silvia Pedroso; Fuzinatto, Cristiane Funghetto; Gonçalves, Renata Amanda; Oscar, Bianca Vicente; Vicentini, Denice Schulz; Matias, William Gerson
Abstract: Among nanomaterials, zinc oxide (ZnO) is notable for its excellent biocidal properties. In particular, it can be incorporated in mortars to prevent biofouling. However, the morphology of these nanomaterials (NMs) and their impact on the action against biofouling are still unknown. This study aimed to assess how the morphology and surface modification can affect the ecotoxicology of ZnO NMs. The morphologies evaluated were nanoparticles (NPs) and nanorods (NRs), and the ZnO NMs were tested pure and with surface modification through amine functionalization (@AF). The toxic effects of these NMs were evaluated by acute and chronic ecotoxicity tests with the well-established model microcrustacean Daphnia magna . The ZnO NMs were characterized by transmission electron microscopy, X-ray diffraction and infrared spectroscopy. The EC5048h to D. magna indicated higher acute toxicity of ZnO@AF NRs compared to all tested NMs. Regarding the chronic test with D. magna, high toxic effects on reproduction and longevity were observed with ZnO@AF NRs and effects on growth were observed with ZnO NRs. In general, all tested ZnO NMs presented high toxicity when compared to the positive control, and the NRs presented higher toxicity than NPs in all tested parameters, regardless of the form tested (pure or with surface modification). Additionally, the pathways of ecotoxicity of the tested ZnO NMs was found to be related to combined factors of Zn ion release, effective diameter of particles and NM internalization in the organism. Graphical abstract: Image 1 Highlights: Surface and morphological modification of ZnO NMs can alter their toxicity. ZnO@AF NR presented the higher acute toxicity to D. magna from all tested NM. Zn release and effective diameter of NM particles contribute together to ZnO NM ecotoxicity. ZnO NMs can be also internalized by D. magna, aggravating their toxic effects.